Dynamic Flow Alteration Index for Complex River Networks With Cascading Reservoir Systems. Issue 1 (29th December 2021) - Kumar, Hemant; Hwang, Jeongwoo; Devineni, Naresh; Sankarasubramanian, A.
Abstract: Large dams degrade the river's health by heavily regulating the natural flows. Despite a long history of research on flow regulation due to dams, most studies focused only on the impact of a single dam and ignored the combined impact of flow regulation on a river network. We propose a new Dynamic Flow Alteration Index (DFAI) to quantify the local and cumulative degree of regulation by comparing the observed controlled flows with the naturalized flows based on a moving time horizon for the highly regulated Colorado River Basin. The proposed DFAI matches closely to dam's localized regulation for headwater gages and starts to diverge as we move downstream due to increase in cumulative impact of the dams. DFAI considers the impact of dam operations on flow characteristics such as shifting of peak flow occurrence and dampening of peak flows. DFAI estimates the degree of regulation to be small for upstream dams and finds the maximum network regulation to be 2.52 years at Glen Canyon reservoir. DFAI also successfully captures the reduction in cumulative regulation when dam operations (e.g., Hoover Dam) bring the altered flow in synchronization with natural regime due to downstream flow requirements. The impact of San Juan River Basin Recovery Implementation Program is also captured by DFAI as the reduction in network regulation drops by 1.5 years for Navajo Dam. Our findings using DFAI suggest the need to develop naturalized flows for major river basins to quantify the flow alteration under continually changing climate and human influences. Key Points: A new Dynamic Flow Alteration Index is proposed to compute the cumulative degree of regulation for complex river networks The time‐varying regulation metric captures the human influence due to reservoir operations and water management Estimated local and cumulative regulation compare well against traditionally used residence time estimates